Structure of Negotiation Language Used By Sellers And Buyers In The Markets of Surakarta With Different Ethnic Backgrounds - Afdzulah, Amdan; Susiati, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to analyze the negotiation language structure used by sellers and buyers from different ethnic backgrounds in traditional markets in Surakarta. The study examines how ethnic diversity affects negotiation strategies and communication styles in markets such as Sidodadi Market, Gede Market, Triwindu Market, Klewer Market, Ngarsopuro Market, Sekaten Market, and Kliwon Market. Methodology: Using qualitative methods and descriptive analysis, data were collected through interviews and field observations. Results: The results show that the negotiation structure-which includes orientation, request, offer, agreement, and closing-remains consistent across markets. However, language variations reflected the ethnic backgrounds of the participants, with Javanese, Indonesian, Mandarin, English, Russian, Arabic, and Sundanese frequently used. Negotiation strategies also varied, with Javanese-dominated markets emphasizing social harmony, while multiethnic markets, such as Gede Market and Ngarsopuro Market, favored efficiency. Applications/Originality/Value: This research emphasizes the important role of cultural and ethnic diversity in shaping language and negotiation strategies in Surakarta's traditional markets.